2017
DOI: 10.1021/acsomega.6b00468
|View full text |Cite
|
Sign up to set email alerts
|

Fitting Single-Walled Carbon Nanotube Optical Spectra

Abstract: In this work, a comprehensive methodology for the fitting of single-walled carbon nanotube absorption spectra is presented. Different approaches to background subtraction, choice of line profile, and calculation of full width at half-maximum are discussed both in the context of previous literature and the contemporary understanding of carbon nanotube photophysics. The fitting is improved by the inclusion of exciton–phonon sidebands, and new techniques to improve the individualization of overlapped nanotube spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 74 publications
1
66
0
Order By: Relevance
“…The J-V curve of the optimized devices is displayed in Figure 2b and the corresponding photovoltaic parameters are summarized in Table 1. [22] The peak at 570 nm in the EQE spectrum originates from the S 22 transition in (6,5) SWCNTs. A comparison to other works on SWCNT:fullerene solar cells is given in Table 1.…”
Section: Photovoltaic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The J-V curve of the optimized devices is displayed in Figure 2b and the corresponding photovoltaic parameters are summarized in Table 1. [22] The peak at 570 nm in the EQE spectrum originates from the S 22 transition in (6,5) SWCNTs. A comparison to other works on SWCNT:fullerene solar cells is given in Table 1.…”
Section: Photovoltaic Performancementioning
confidence: 99%
“…[15] Concepts such as small molecule:fullerene active layers aim to use simple, well-defined molecules instead of polymers, which always exhibit a distribution in chain length altering their properties. [20,21] The high absorption coefficients in the nIR wavelength regime [22,23] make SWCNTs well suited to IR-sensitive OSCs via a ternary concept or in a binary blend with SWCNTs as the main absorber in the IR region.Previously it was shown that SWCNTs work in a type-II heterojunction scheme acting either as an electron acceptor in combination with a polymer or as the electron donor in combination with C 60 or [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM). The incorporation of SWCNTs in OSCs or other organic devices [16][17][18][19] (near-infrared (nIR) detectors, nIR lightemitting diodes (LEDs), and field-effect transistors (FETs)) is based on several advantageous key factors that allow to boost device performances.…”
mentioning
confidence: 99%
“…We assigned all the features in the absorption spectra to S 11 , S 22 , S 33 excitonic transitions of semiconducting nanotubes evaluated from PLE map. By fitting the optical absorption spectrum (Figure S1, Supporting Information) using common procedures we show that the sorting purity of the obtained semiconducting SWCNT seeds is high and estimate the quantity of residual metallic nanotubes to be below optical quantification limits, roughly less than 1% …”
Section: Resultsmentioning
confidence: 99%
“…By fitting the optical absorption spectrum ( Figure S1, Supporting Information) using common procedures we show that the sorting purity of the obtained semiconducting SWCNT seeds is high and estimate the quantity of residual metallic nanotubes to be below optical quantification limits, roughly less than 1%. [24,25] The advantages of using ST-cut quartz as a substrate and a drop-casting method of depositing nanotube seeds for the VPE growth of SWCNT have been reported by several groups. The high smoothness of the annealed in air ST-cut quartz (roughness is less than 1 nm) is beneficial for the growth of long nanotubes.…”
Section: Resultsmentioning
confidence: 99%
“…Waveguides and electrodes were then simultaneously patterned by defining an aluminum etch mask (20 nm) via ebeam lithography and metal evaporation. The (n, m) CNT distribution in suspension was determined by fitting the absorption spectrum using the PTFfitcode, [36] as shown in Figure S4 (Supporting Information). The distance between the source-drain electrodes is 800 nm, leaving a gap of 180 nm between each electrode and the waveguide.…”
Section: Methodsmentioning
confidence: 99%